(untitled) (The Voz a Vos Bulletin, 2024)
This dramaturgical text is the result of the permanent need to listen to the voices of those who, due to violence in our country and the world, have lost their lives at the hands of armed groups. It is the conversation of two hunks of men waiting in a common grave for someone to come and tell them what day it is. With a great Beckian influence and the song Bohemian Rhapsody by Queen written in 2011.